Penegakan Hukum Terhadap Terdakwa Fatriadi Ruslan dalam Kasus Peredaran Narkotika di Mataram (Nomor 73/Pid.Sus/2023/PN Mt) - Al Fajar, Muhammad Din; Lubis, Anggi Rahmadina; Sebayang, Blesscherise; Gultom, Dina Sarahani; Diva, Kanaya Salsha; Dalimunthe, Nabila Alya Safwana; Rumahorbo, Noya Callista (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2024)
Abstract:Narcotics trafficking is a serious problem faced by many countries, including Indonesia, with detrimental impacts on individual physical and mental health as well as social and economic stability. Abuse of narcotics, especially Class I narcotics such as methamphetamine (shabu), not only causes dependence and mental disorders, but also becomes the main commodity in the illegal narcotics trade. The Indonesian government, through Law Number 35 of 2009 concerning Narcotics, has regulated strict sanctions for perpetrators of narcotics abuse and distribution. A case study in the Karang Bagu neighborhood, Mataram, shows the active role of the community in eradicating narcotics trafficking through collaboration with the police, who succeeded in uncovering methamphetamine transactions by the suspect Fatriadi Ruslan. Strict law enforcement, such as the application of Article 112 paragraph (1) in this case, is expected to be able to provide a deterrent effect and reduce the number of narcotics trafficking in Indonesia.Keywords: Narcotics distribution, methamphetamine (shabu), law enforcement. AbstrakPeredaran narkotika merupakan salah satu masalah serius yang dihadapi banyak negara, termasuk Indonesia, dengan dampak yang merugikan kesehatan fisik dan mental individu serta stabilitas sosial dan ekonomi. Penyalahgunaan narkotika, khususnya narkotika Golongan I seperti metamfetamin (sabu), tidak hanya menimbulkan ketergantungan dan gangguan mental, tetapi juga menjadi komoditas utama dalam perdagangan narkotika ilegal. Pemerintah Indonesia melalui Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika telah mengatur sanksi ketat bagi pelaku penyalahgunaan dan peredaran narkotika. Studi kasus di Lingkungan Karang Bagu, Mataram, menunjukkan peran aktif masyarakat dalam memberantas peredaran narkotika melalui kerja sama dengan aparat kepolisian, yang berhasil mengungkap transaksi sabu oleh tersangka Fatriadi Ruslan. Penegakan hukum yang tegas, seperti penerapan Pasal 112 ayat (1) dalam kasus ini, diharapkan mampu memberikan efek jera dan menurunkan angka peredaran narkotika di Indonesia.Kata kunci : Peredaran narkotika, Metamfetamin (sabu), Penegakan hukum.